2001
DOI: 10.1016/s1388-9842(00)00150-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, prognosis and predictors of improvement of systolic left ventricular function in patients with ‘classical’ clinical diagnosis of idiopathic dilated cardiomyopathy

Abstract: Ž. In patients with dilated cardiomyopathy DCM of different aetiologies, a variable frequency of improvement in the left Ž . ventricular LV systolic function has been reported, while in patients with a 'classic' idiopathic DCM, the frequency of improvement is still under debate, and clinical and haemodynamic predictors of recovery of the LV function are needed. The aim of the present study was to determine the frequency of improvement in the LV systolic function in idiopathic DCM and to identify predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…It has been reported that the prevalence of spontaneous recovery in alcoholic cardiomyopathy is relatively high. 18 The pathologic studies shown that myocyte hypertrophy, fibrosis, and nuclear changes are significantly less frequent in alcoholic cardiomyopathy compared with idiopathic DCM. 19 However, in the present DE(+) group, cardiomyopathy without definite cause (namely, idiopathic) was the most frequent (90.5%), as expected.…”
Section: De and Prognosis Of Nicmmentioning
confidence: 99%
“…It has been reported that the prevalence of spontaneous recovery in alcoholic cardiomyopathy is relatively high. 18 The pathologic studies shown that myocyte hypertrophy, fibrosis, and nuclear changes are significantly less frequent in alcoholic cardiomyopathy compared with idiopathic DCM. 19 However, in the present DE(+) group, cardiomyopathy without definite cause (namely, idiopathic) was the most frequent (90.5%), as expected.…”
Section: De and Prognosis Of Nicmmentioning
confidence: 99%
“…[5][6][7][8] These observations have significant clinical impact on selecting patients for cardiac transplantation, because of the shortage of donor hearts. Baseline clinical variables associated with RR were shorter duration of symptoms, 5,6 a history of hypertension, 6-8 nonischemic cause of heart failure, 8 absence of diabetes mellitus, 7,8 carvedilol therapy, 7,8 higher serum sodium level, 5 and lower atrial pressure.…”
Section: Functional Improvement In Heart Failurementioning
confidence: 99%
“…Although myocardial failure is generally considered an irreversible and progressive process characterized by left ventricular (LV) remodeling, some patients with marked LV dysfunction have been reported to show functional improvement or reverse remodeling (RR) after aggressive medical treatment, 1-4 leading many investigators to seek predictors of RR. [5][6][7][8] Echocardiographic indexes of ventricular systolic and diastolic function have become indispensable in evaluating patients with LV dysfunction, and have been tested as prognostic markers. [9][10][11][12][13] The recently introduced Doppler tissue imaging (DTI) technique provides unique information regarding regional myocardial function and ventricular longitudinal contractility (LC).…”
mentioning
confidence: 99%
“…In addition, only patients with recent onset cardiomyopathy (≤ 9 months) were enrolled in CAT including an unknown number of patients with active myocarditis, since endomyocardial biopsies were not performed at the majority of participating centers. Significant improvements of LV dysfunction have been observed in approximately one third of patients, after the initial diagnosis of nonischemic dilated cardiomyopathy has been made [5][6][7][8][9][10]. Improvements of LV dysfunction have been observed even more frequently in patients with "recent-onset cardiomyopathy" [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvements of LV dysfunction have been observed in approximately one third of patients, after the initial diagnosis of nonischemic dilated cardiomyopathy has been made [5][6][7][8][9][10]. Improvements of LV dysfunction have been observed even more frequently in patients with "recent-onset cardiomyopathy" [6][7][8]. This may be explained by a high prevalence of "healing" myocarditis in these patients [6,10].…”
Section: Introductionmentioning
confidence: 99%